2022
DOI: 10.3389/fpls.2022.1000024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of the aldehyde dehydrogenase gene superfamily in Arabidopsis thaliana – searching for the functional key to hypoxia tolerance

Abstract: Flooding entails different stressful conditions leading to low oxygen availability for respiration and as a result plants experience hypoxia. Stress imposed by hypoxia affects cellular metabolism, including the formation of toxic metabolites that dramatically reduce crop productivity. Aldehyde dehydrogenases (ALDHs) are a group of enzymes participating in various aspects of plant growth, development and stress responses. Although we have knowledge concerning the multiple functionalities of ALDHs in tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Through oxidation and dehydrogenation, ALDH can convert aldehydes into nontoxic carboxylic acids, which provide protection and detoxification to living organisms but are also associated with stress. ALDHs are upregulated in response to various forms of stress in organisms, including bacteria (due to environmental and chemical stress) [32,37], plants (such as dehydration, salinity, and oxidative stress) [15,38,39], yeast (ethanol exposure and oxidative stress) [18,40], mammals (from oxidative stress and lipid peroxidation) [41], and M. oryzae (which promotes oxidative and reductive stress tolerance) [21]. In this study, we examined the responses of seven ALDH-deficient mutants to different stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through oxidation and dehydrogenation, ALDH can convert aldehydes into nontoxic carboxylic acids, which provide protection and detoxification to living organisms but are also associated with stress. ALDHs are upregulated in response to various forms of stress in organisms, including bacteria (due to environmental and chemical stress) [32,37], plants (such as dehydration, salinity, and oxidative stress) [15,38,39], yeast (ethanol exposure and oxidative stress) [18,40], mammals (from oxidative stress and lipid peroxidation) [41], and M. oryzae (which promotes oxidative and reductive stress tolerance) [21]. In this study, we examined the responses of seven ALDH-deficient mutants to different stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Grape ALDH genes are essential for grape development, and some have been observed to be reactive to salt stress or drought [6]. Comparative genomic analyses of the ALDH gene superfamily in Arabidopsis thaliana have demonstrated that ALDH is a critical factor in hypoxia tolerance [15]. The role of ALDH in both human and yeast cells has also been extensively studied, as ALDH removes detrimental aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 24 ALDH families (ALDH1-24) were reported. Among them, ALDH2 and ALDH3 families are the most abundant in plants, with the former oxidizing mainly short-chain fatty aldehydes and the latter preferentially oxidizing medium-to long-chain fatty aldehydes (Stiti et al, 2021;Guan et al, 2022). Of the three genes encoding ALDH, BsALDH1 and BsALDH2 were classified as ALDH3, and BsALDH3 was classified as ALDH2, which contributed to the conversion of short or medium-chain fatty aldehydes to the corresponding fatty acids.…”
Section: Molecular Mechanism Of Biosynthesis Of Volatilesmentioning
confidence: 99%